3-dimensional analysis of asynchronous motor with finite element method - Korkmaz, Sevcan Aytac; Kurum, Hasan (Elsevier Science Bv, 2015)
In this article, it will be focused on 3-dimensional analysis of an asynchronous motor with finite element method. Analysis of finite element of an asynchronous motor was performed with the help of a program developed by Maxwell 3D software program. Analysis of an asynchronous motor was conducted by calculating magnetic flux density B, current densities and as a result moment value. (C) 2015 The Authors. Published by Elsevier Ltd.
5th International Conference on New Horizons in Education (INTE) -- JUN 25-27, 2014 -- Paris, FRANCE
Keywords: Induction Motor; Finite element Method; Maxwell 3D